Identification of wetland conservation and restoration priorities in regions of oil extraction in the Yellow River Delta using circuit theory modelling - Yuru Wu; Tao Hong; Ling Meng; Luxiang Xiao; Yunzhao Li; Xiaoli Bi (Ecological Indicators, 2023)
Oil exploration fragments coastal wetland habitats, which often leads to biodiversity loss and ecosystem degradation. Assessing the negative effects of oil infrastructures at the landscape scale is critical for practical coastal wetland management and the planning of protected areas (PAs). However, information gaps involving wetland connectivity and oil exploration exist in current conservation, which limit the efficiency of PAs.Here, we used a GIS-based circuit theory model (Circuitscape) and high-resolution remote sensing data to simulate the movement patterns of random species and to elucidate the effects of oil wells on their connective elements in four types of wetlands (mudflat, saline marsh, shrub wetland and forest wetland) in the Yellow River Delta (YRD), China. The effectiveness of the Yellow River Delta Nature Reserve (YRDNR) in protecting wetland connectivity was evaluated. A planning framework to optimize wetland conservation and restoration by Linkage Mapper was then provided to improve the landscape connectivity of oil well-disturbed wetlands in this region.The results showed that oil wells significantly decreased wetland connectivity and altered their connective elements in the four wetlands of the YRD. Both the resistance of wetland species movement and the heterogeneity of species dispersal have increased. The length of potential corridors and areas possessing barriers to movement have increased by 126 km (20%) and 51 km2 (120%), respectively. Areas with pinch points that promote species movements, however, decreased by 1178 km2 (60%). The YRDNR protected less than 50% of the key corridors and ecological nodes, considering the impacts of oil wells. Mudflat is seriously affected by oil wells in the YRDNR. Consequently, new alternative corridors produced by oil wells and pinch areas at high risk of impacts by oil wells have the highest protection priorities, whereas those permeable barrier areas, such as croplands and paddy fields, have the highest restoration priorities. The results also illustrated the importance of rivers and water bodies as potential shelters for wetland species.Our research suggests that circuit theory model is an effective planning tool to quantify the negative impacts of oil activities and to identify the protection or restoration priorities of ecological hot spots which are unable to be detected by traditional PAs method. This work provides guides for improving landscape connectivity and specifying target habitats for coastal conservation management.